4D magnetic resonance velocity mapping of blood flow patterns in the aorta in young vs. elderly normal subjects - Bogren, Hugo G.; Buonocore, Michael H. (Journal of magnetic resonance imaging, 1999)
Four‐dimensional magnetic resonance MR velocity mapping was developed to study normal flow patterns in the thoracic aorta using time‐resolved cardiac gated three‐directional velocity data. Sixteen normal subjects were studied, one young group (average age 31 years) and one group with elderly people (average age 72 years). Blood flowed in a right‐handed helix from the ascending aorta to the aortic arch. A straight flow pattern or a left‐handed helix was seen in the descending aorta. Blood flow was never parabolic. Blood flowed forward in early systole, retrograde in mid‐to‐end systole, and forward again in diastole in all subjects as a basic pattern. Continuous retrograde flow over a long distance was not seen, but blood entered a retrograde flow column at various levels. In young people blood passed from the aortic valve to the mid‐descending aorta in less than one heartbeat. In people in their sixties it took two heartbeats and in people older than 78 years, it took three heartbeats. The maximum systolic forward velocities were higher in young subjects than in elderly while the retrograde velocities were lower. J. Magn. Reson. Imaging 1999;10:861–869. © 1999 Wiley‐Liss, Inc.